Role of the Consumption of Fucoidans and Beta-Glucans on Human Health: An Update of the Literature [Rol del Consumo de Fucoidanos y Betaglucanos en la Salud Humana: Artículo de Actualización] - Florez-Mendez, J (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2019)
Bioactive compounds are substances present in low doses in foods mostly from the plant kingdom. Their consumptioncan influence physiological or cellular processes and has abeneficial effect on health. Fucoidans and beta-glucans are bioactive compounds that share the characteristic of being carbohydrates of the polysaccharide type, specifically of the soluble fiber kind. These compounds can be found in foods available in Chile and part of the Chilean diet; foods include, brown algae and some cereals. The concentration of the secompounds in foods is variable, and depends on factors like season, cultivation, germination, and method of preparation and conservation. The current literature shows the potential beneficial effects of fucoidan and beta-glucans compounds in human health, which include: Anticoagulant, immune modulator and antidiabetic and immune modulating. The effects depend, among other factors, on their bioavailability and molecular weight. The objective of this review was to describe the potential beneficial effects of these bioactive compounds, analyze their characteristics and properties, and provide consumption recommendations that may lead to achieving the expected beneficial effects. To that end, relevant and recent scientific literature was analyzed. © 2019, Sociedad Chilena de Nutricion Bromatologia y Toxilogica. All rights reserved.